Crystallinity improvement of poly(heptazine imide) for high photocatalytic hydrogen evolution. (December 2022) - An, Wenshu; Zhi, Xiaojuan; Zhai, Boyin; Niu, Ping; Wang, Shulan; Li, Li
Abstract: As the crystalline phase of g-C3 N4, poly(heptazine imide) (PHI) is attracting increasing attention recently due to its advantages in light absorption and charge transfer compared with the commonly studied g-C3 N4 with Melon structure. Crystallinity engineering to further enhance its crystallinity may significantly improve the photocatalytic performances and thus the effective strategy is highly desirable. Herein, we propose a post-thermal treatment assisted ionothermal protocol to achieve the crystallinity elevation of PHI. By simply adding an extra annealing step in thermal polycondensation of precursors to tune Melon structure, the recondensation process for PHI synthesis was directly modified, leading to the formation of high-crystalline product. The synthesized materials therefore presented decreased interlayer stacking distance, narrowed bandgap and improved charge transfer/separation kinetics, which remarkably enhanced the visible-light photocatalytic activities of PHI. This work provides references for structural modifications of high-crystalline g-C3 N4 based materials, which may inspire new ideas for the design of high-performance photocatalysts. Graphical abstract: Image, graphical abstract